2010
DOI: 10.1074/mcp.m110.001362
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Matrix Proteome Analysis of Drosophila melanogaster

Abstract: The nucleus is a highly structured organelle and contains many functional compartments. Although the structural basis for this complex spatial organization of compartments is unknown, a major component of this organization is likely to be the non-chromatin scaffolding called nuclear matrix (NuMat). Experimental evidence over the past decades indicates that most of the nuclear functions are at least transiently associated with the NuMat, although the components of NuMat itself are poorly known. Here, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…NuMat preparations from these embryos were identified by LC-MS/MS. While our earlier report shed light on the changing pattern of the NuMat proteome during development (Kallappagoudar et al 2010), this study shows that NuMat proteome is indeed dynamic with remarkable variation between the two developmental stages. Thus, this analysis establishes a link between the dynamics of both embryonic development as well as nuclear architecture.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…NuMat preparations from these embryos were identified by LC-MS/MS. While our earlier report shed light on the changing pattern of the NuMat proteome during development (Kallappagoudar et al 2010), this study shows that NuMat proteome is indeed dynamic with remarkable variation between the two developmental stages. Thus, this analysis establishes a link between the dynamics of both embryonic development as well as nuclear architecture.…”
Section: Introductionmentioning
confidence: 88%
“…In fact, in a recent study, an extensive analysis of NuMat proteome composition has reflected the rich variety of functional categories of proteins associated with NuMat, providing further implications of its role in the diverse nuclear processes. These proteins included structural proteins, heat shock proteins, chaperones, DNA binding and mitotic scaffolding proteins, chromatin remodeling proteins, transcription-and translation-associated proteins and also ribosomal proteins (Kallappagoudar et al 2010). Taken together, these studies have further strengthened the concept of NuMat being associated with processes such as embryonic development and differentiation and hence the interplay between the dynamics of nuclear architecture and regulation of gene expression during these key molecular events.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Hsp26 has been found in the nuclear matrix of Drosophila Schneider 2 (S2) cells and embryos together with Hsp27 (Kallappagoudar et al 2010 ). To our knowledge, this is the fi rst report showing a nuclear localization for this cytoplasmic sHsp.…”
Section: Intracellular Localizationmentioning
confidence: 98%
“…4E). Proteomic analyses have shown that other cohesin subunits also associate with the nuclear envelope (Kallappagoudar et al, 2010), and it is possible that such interactions might stabilize interactions between the homologous chromatids. Considering that exchange between the chromatids requires their precise alignment over extensive regions around homologous recombination intermediates, it is tempting to speculate that the Brca2-mediated Pds5-Pds5 interactions might serve the simultaneous clamping of two cohesin rings around the homologs.…”
Section: Discussionmentioning
confidence: 99%